High‐fat diet‐induced obesity worsens TH2 immune response and immunopathologic characteristics in murine model of eosinophilic oesophagitis. Issue 2 (26th December 2019) - Silva, Flávia Márcia de Castro e; Oliveira, Erick Esteves de; Ambrósio, Marcilene Gomes Evangelista; Ayupe, Marina Caçador; Souza, Viviane Passos de; Gameiro, Jacy; Reis, Daniele Ribeiro de Lima; Machado, Marco Antonio; Macedo, Gilson Costa; Mattes, Joerg; Ferreira, Ana Paula
Abstract: Background: Eosinophilic oesophagitis (EoE) is an emergent chronic immune‐mediated disease of the oesophagus, which affects both children and adults. It is clinically characterized by dysphagia, food impaction and oesophageal eosinophilia. Epidemiological studies indicate that obesity can worsen allergic symptoms; however, its effect on EoE immunopathological response has not been evaluated yet. This study aimed to assess the effect of obesity on allergic inflammation and T helper‐2 profile in an EoE experimental model. Methods: Obesity was induced by high‐fat feeding. After 7 weeks of diet, male BALB/c mice were subcutaneously sensitized and orally challenged with OVA. Results: Obesity itself induced a significant mast cell and eosinophil accumulation in the oesophagus, trachea, gut and lung. After allergy induction, this number was higher, when compared to lean‐allergic mice. Moreover, obese‐allergic mice showed higher remodelling area, in the oesophagus, associated with higher IL‐5 and TSLP mRNA expression. In contrast, FoxP3 and IL‐10 were less expressed in comparison with lean‐allergic mice. In addition, the amount of CD11c + MHCII + PDL1 + dendritic cells was reduced, while the number of CD11c + MHCII + CD80 + DCs and CD3 + CD4 + GATA3 + IL‐4 + cells was increased in obese‐allergic mice in the spleen and lymph nodes when compared to lean‐allergic mice. Conclusion: Obesity aggravated the immune histopathological characteristics in the EoE experimental model, which was associated with the reduction in the regulatory profile, and the increased inflammatory cells influx, related to the TH 2 profile. Altogether, the data provide new knowledge about obesity as a risk factor, worsening EoE symptoms, and contribute for future treatment strategies for this specific profile.